Comparative analysis of oral microbiome from Zang and Han populations living at different altitudes. (January 2021) - Hao, Yu; Tang, Can; Du, Qilian; Zhou, Xuedong; Peng, Xian; Cheng, Lei
Highlights: The first study to probe the impact of altitude and ethnicity on the oral microbiome. Altitude may have a significant impact on the oral microbiome composition. The Zang population in high altitude had the highest abundance of P. gingivalis. Abstract: Objectives: The aim of this study was to obtain greater insight into the environmental and genetic factors affecting the oral microbiome. Design: To this end, we investigated the oral microbiome composition in Han and Zang populations living at different altitudes. The saliva microbiome in 115 individuals from Zang and Han populations living at different altitudes was analyzed using the 16 s rRNA gene sequencing method on the Illumina MiSeq platform. The dominant species in the oral microbiome were verified by quantitative real-time polymerase chain reaction (qPCR) analysis. Results: The Han population, living at an altitude of 500 m, had higher microbiome diversity than the Zang population living at altitudes of 3000–4000 m. People living at 3000 m had a higher relative abundance of Leptothrix genus, but people living at 500 m had a higher relative abundance of Capnocytophaga genus according to Lefse difference analysis (P < 0.05). Compared to the Zang population, the Han population had higher relative abundances of Porphyromonas and Treponema genus organisms, especially Porphyromonas (P < 0.001). qPCR analysis confirmed that people living at high altitudes had the highest relative abundance of Porphyromonas gingivalis (P < 0.01). Conclusions: This study showed that both genetics and the environment had significant influences on the oral microbiome composition. The study proposed a meaningful research direction to explore the relationship between different ethnic and altitude groups and oral diseases, such as periodontal diseases.